Anchoring of CsPbBr3 perovskite quantum dots on BN nanostructures for enhanced efficiency and stability: a comparative study. Issue 3 (23rd December 2020) - Yu, Mengmeng; He, Xin; Li, Danyang; Lin, Jing; Yu, Chao; Fang, Yi; Liu, Zhenya; Guo, Zhonglu; Huang, Yang; Tang, Chengchun
Abstract : Anchoring of CsPbBr3 perovskite quantum dots on BN nanostructures could be an effective way to keep them from degradation under certain conditions, however, their performances rely on the characteristics of the utilized BN nanostructures strongly. Abstract : All-inorganic CsPbX3 (X = Cl, Br, I) perovskite quantum dots (QDs) are prone to degradation under certain conditions, such as air, ultraviolet light and high temperature, which limits their practical applications. Here, we report the utilization of four kinds of BN nanomaterials, namely BN nanosheets (BNNS), BN nanofibers (BNNF), commercial BN nanosheets (C-BNNS) and BN nanospheres (BNNP), as carriers for supporting CsPbBr3 (CPB) QDs to obtain a series of CPB/BN nanocomposites. A comprehensive study on the microstructures, photoluminescence (PL) properties, and the stabilities of various nanocomposites under different conditions (air, ultraviolet light and high temperature) has been carried out. The results show that the addition of BN can not only retain the excellent PL properties of CsPbBr3 QDs, but also improve their photostabilities, long-term storage stabilities, and thermal stabilities. Comparative studies also demonstrate that BN nanomaterials with different structures have great influence on the properties of CPB/BN nanocomposites. BNNS and BNNF with high specific surface areas and surface functional groups can provide a large number of adsorption sites for the uniform anchoring of CsPbBr3 QDs, thus effectively improving the PL and stability performance of the nanocomposites. In particular, compared with the QDs loaded on the surface of nanofibers, the CsPbBr3 QDs can be better protected by multi-layered nanosheets with a flexible feature and folds, thereby showing higher crystallinity. Finally, the best-performing CPB/BNNS nanocomposite is made into a white LED device, which emits bright white light with a correlated color temperature of 5531 K. The findings can provide an effective guiding strategy for the development of high-performance BN-based nanocomposites, which are of great significance due to their great potential applications in solid-state lighting.